FGF expression in HPV16-positive and -negative SCC after treatment with small-molecule tyrosine kinase inhibitors and everolimus - Huber, Lena; Birk, Richard; Knüttel, Manuel Thomas; Rotter, Nicole; Aderhold, Marc Christoph; Scherl, Claudia; Lammert, Anne; Jungbauer, Frederic; Kramer, Benedikt (Anticancer research, 2020)
Background: Targeted therapies in the treatment of head and neck squamous cell carcinoma (HNSCC) are subject to extensive research. Different mutations of genes belonging to the fibroblast growth factor (FGF) family have been detected in HNSCC. In this study, we examined the expression of FGF1 and FGF2 after treatment with small-molecule tyrosine kinase inhibitors (TKIs) and an inhibitor of mechanistic target of rapamycin (mTOR) in vitro using human papillomavirus (HPV)-positive and -negative SCC lines. Materials and Methods: Cells of two human HPV-negative cell lines (UMSCC-11A/-14C) and one HPV-positive cell line (CERV196) were incubated with 20 μmol/l of erlotinib, gefitinib, nilotinib, dasatinib, or everolimus for 24-96 h. Cell proliferation was assessed by proliferation assay and the protein concentrations of FGF1 and FGF2 by sandwich enzyme-linked immunosorbent assay. For statistical analysis, the results were compared with those for untreated HPV-negative SCC cells. Results: FGF1 and FGF2 were detected in all three tested cell lines. The tested TKIs significantly (p<0.05 reduced) FGF1 expression in the UMSCC-11A cell line within the first 24 h. At later time points, the tested TKIs and everolimus significantly (p<0.05) increased FGF1 and FGF2 expression in HPV-negative and -positive cancer cell lines. The effect was stronger in the HPV-positive cell line. Conclusion: Alterations in FGF signalling are considered to be relevant drivers of tumourigenesis in some HNSCCs. Our results show that the expression of FGF1 and -2 can be influenced effectively by small-molecule TKIs and everolimus. Based on our data, future research should include combinations of specific FGF inhibitors, mTOR inhibitors and other TKIs in the treatment of HNSCC and research on FGF-mediated drug escape mechanisms.